2011
DOI: 10.1007/s00134-011-2297-y
|View full text |Cite
|
Sign up to set email alerts
|

A physiologic comparison of proportional assist ventilation with load-adjustable gain factors (PAV+) versus pressure support ventilation (PSV)

Abstract: PAV+ improves patient-ventilator interaction, significantly reducing the incidence of end-expiratory asynchrony and increasing the time of synchrony.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
2
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 23 publications
3
32
2
8
Order By: Relevance
“…22 In prospective observational studies comparing PAVϩ and PSV during the weaning process regarding tolerance, duration of invasive mechanical ventilation, and clinical outcomes, no significant differences were found among the groups in mechanical ventilation duration, re-intubation rate, mortality, need for tracheostomy, and percentage of post-extubation noninvasive ventilation, indicating that PSV and PAVϩ could be considered clinically equivalent in relation to weaning. 23,24 A pilot study demonstrated the safety and feasibility of the PAVϩ algorithm for weaning, 25 confirming the findings of our study. The time that T-tube group remained in the trial was significantly shortened by 10 min, which demonstrates the staff's confidence in the T-tube; however, the testing time did not affect the incidence of extubation failure or clinical outcomes.…”
Section: Discussionsupporting
confidence: 84%
“…22 In prospective observational studies comparing PAVϩ and PSV during the weaning process regarding tolerance, duration of invasive mechanical ventilation, and clinical outcomes, no significant differences were found among the groups in mechanical ventilation duration, re-intubation rate, mortality, need for tracheostomy, and percentage of post-extubation noninvasive ventilation, indicating that PSV and PAVϩ could be considered clinically equivalent in relation to weaning. 23,24 A pilot study demonstrated the safety and feasibility of the PAVϩ algorithm for weaning, 25 confirming the findings of our study. The time that T-tube group remained in the trial was significantly shortened by 10 min, which demonstrates the staff's confidence in the T-tube; however, the testing time did not affect the incidence of extubation failure or clinical outcomes.…”
Section: Discussionsupporting
confidence: 84%
“…Higher PTP values may indicate increased activity of respiratory muscles, which likely contributed to redistribution of ventilation towards dependent regions during PAV. [8][9][10][11][12][13][14] Dependent, gravitational dependent lung regions (dorsal); nondependent, gravitational nondependent lung regions (ventral). a p < .05 vs. PSV; b p < .05 vs. noisy PSV; c p < .05 vs. dependent/nondependent region within the same group, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, PAV may lead to increased variation in tidal volume (V T ) and respiratory rate (RR) (3), provided the patient's respiratory drive also shows increased variability. However, studies on PAV have focused on aspects of lung function and patient-ventilator asynchrony (3,(11)(12)(13), and its impact on lung damage and inflammation has not been determined.…”
mentioning
confidence: 98%
“…The value of the P^^^ _, p^^î could, therefore, have been underestimated in some patients. However, because tidal volume is chosen by the patient on a breath-by-breath basis (23) and the insufflation time is close to the neural inspiratory time (23,32) whatever the level of assistance (16), the risk of significant dynamic hyperinflation is low in PAV-I- (22). Eurthermore, Appendini et al ( 15) showed that adding continuous positive airway pressure during proportional assist ventilation dramatically reduced the level of PEEPi in chronic obstructive pulmonary disease (COPD) patients with a high basal level of PEEPi.…”
Section: Limitationsmentioning
confidence: 99%